The Progressive Reduction in the Ovarian Reserve in Young Women After Anticancer Treatment - Krawczuk-Rybak, M.; Leszczynska, E.; Poznanska, M.; Zelazowska-Rutkowska, B.; Wysocka, J. (Hormone and Metabolic Research, 2013)
Anticancer treatment can disturb gonadal function and deplete the primordial follicle pool, leading to premature menopause. We made a prospective analysis of serum hormone levels in young female cancer survivors who had been treated during childhood and adolescence. Serum anti-Müllerian hormone (AMH) as a marker of ovarian reserve, FSH, LH, and estradiol were measured in 33 women treated previously (6–11 years earlier) for Hodgkin Lymphoma, solid tumours, and after bone marrow transplantation, and in 34 healthy controls. The group of survivors was divided according to the risk of gonadotoxicity into the low risk and median risk group (LR+MR), and into the high risk (HR) group. The measurements were repeated after 5 years. In the HR group, AMH levels were significantly lower than in controls (p=0.001) and in the LR+MR group (p=0.006) at the time of the first examination fell progressively after 5 years (p=0.03), whereas elevated FSH values (p=0.053) increased (p=0.001). Unchanged LH values in the first measurement rose in the second one (p=0.001). In the LR+MR group, the levels of AMH and FSH were normal (compared to the control) at baseline, but after 5 years serum AMH decreased (p=0.027) and FSH increased (p=0.008). Our findings indicate that anticancer treatment during childhood and adolescence is associated with a serious, progressive risk of ovarian failure. It is necessary to inform female cancer survivors, especially the high risk patients, about the risk of premature menopause.
Keywords: cancer survivors; gonadotoxicity; fertility; anti-Müllerian hormone; premature menopause